Perspectives on the right to development - Carol C Ngang (Pretoria University Law Press (PULP), 2018)
The last couple of decades has not only witnessed an increased convergence between human rights and development but also a significant shift towards rights-based approaches to development, including especially responsiveness to the fact that development in itself is a human right guaranteed to be enjoyed by all peoples. This edited volume of peer-reviewed papers constitutes the first product resulting from the annual international conference series on the right to development, organised by the Centre for Human Rights, University of Pretoria, and the Thabo Mbeki African Leadership Institute at the University of South Africa. It explores the complex nature of the right to development from a diversified perspective, including from a conceptual, thematic, country and regional points of view. Conceived with the purpose to overshadow dominant economic growth approaches to development, the perspectives on the right to development articulated in this publication seek to locate the developmentalist discourse within the framework of accountability and people-centred development programming, necessitating appropriate policy formulation to ensure the constant improvement in human well-being. The book is written with the aim to reach out to researchers, academics, practitioners and policy makers who desire an in-depth understanding of the right to development as it applies universally.